Eksplorasi Pemanfaatan Docker untuk Mempermudah Pengelolaan Instalasi Komputer di Laboratorium Komputer Teknik Informatika Universitas Kristen Petra - Adi Kurniawan; Henry Novianus Palit; Justinus Andjarwirawan (Jurnal Infra, 2016)
Docker is an application that is based on open source technology that allows developers or anyone to create, run, do experiments and launch application in a container. Docker make the process of packaging application components together quickly in an isolated container, so it can run in local infrastructure without changing configuration on the container. Docker also very light and fast when compared to hypervisor-based virtual machine.Department of Information Engineering of Petra Christian University has a considerable number of students, which the number usually hundreds, while the number of computers in the laboratory of Department of Information number is not as much as the students. With this amount is not comparable, then some students work in the same computer alternately. It makes the students cannot be comfortable working on one computer, because configuring a computer on every lesson is different. Therefore, implementation of Docker application carried out in the laboratory.Docker implementation and RAID storage system and after implementation, testing was done by measuring the speed of docker image transfer. The resulting data were used to development of container system and evaluate the speed of RAID storage system are used.